PENGARUH STRATEGI PROMOSI DAN FASILITAS TERHADAP PEMILIHAN TEMPAT WISATA ANAI LAND - Salma Yetti (JURNAL PUNDI, 2020)
Fast traslate Icon translate The purpose of this study was to determine the effect of promotion strategies and facilities on the selection of anai land tourist attractions. The population of this study was that of anai land tourism visitors in June 2019 with a total of 3,774 visitors. Use the Slovin formula to determine the sample. The number of samples used was 98 respondents. Data collection was carried out by means of a questionnaire measured by a Likert scale. The results showed that the promotion strategy had a positive and significant effect on the choice of tourist attractions as indicated by a significant value of 0.00, while facilities had no positive and significant effect on the choice of tourist attractions indicated by a significant value of 0.801.